1986
DOI: 10.1113/jphysiol.1986.sp015974
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of pulmonary C fibres decreases coronary arterial resistance in dogs.

Abstract: SUMMARY1. A constant-flow preparation was used to assess coronary arterial resistance while activating pulmonary C fibres in chloralose-anaesthetized dogs.2. A Gregg cannula was passed through the left common carotid artery until the tip fitted snugly in the left circumflex coronary artery. The cannula was perfused with blood from the left femoral artery and blood flow through the cannula was maintained constant with a perfusion pump. Perfusion pressure in the coronary artery was measured from a side arm in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Although data from Duncker et al indicate that the withdrawal of parasympathetic activity may facilitate β-adrenoceptor dilation in swine during exercise (280), the effects of the parasympathetic nervous system on the control of coronary blood flow are quite modest under most physiologic conditions (198, 280, 332, 335). However, there is evidence to support a role for parasympathetic coronary vasodilation in the carotid chemoreceptor reflex (430,442,700,703,950), Bezold-Jarisch reflex (186,330,1027), and during activation of afferent vagal C fibers in the lung (187, 734). …”
Section: Neural Controlmentioning
confidence: 99%
“…Although data from Duncker et al indicate that the withdrawal of parasympathetic activity may facilitate β-adrenoceptor dilation in swine during exercise (280), the effects of the parasympathetic nervous system on the control of coronary blood flow are quite modest under most physiologic conditions (198, 280, 332, 335). However, there is evidence to support a role for parasympathetic coronary vasodilation in the carotid chemoreceptor reflex (430,442,700,703,950), Bezold-Jarisch reflex (186,330,1027), and during activation of afferent vagal C fibers in the lung (187, 734). …”
Section: Neural Controlmentioning
confidence: 99%
“…Even in studies using generally similar methods, the efferent pathways mediating the coronary vasomotor response to a given afferent input may vary. Thus, in chloralose-anaesthetized dogs, Clozel et al (1985) found that the coronary vasodilatation evoked by stimulating pulmonary C fibres was blocked by atropine, whereas Ordway & Pitetti (1986) found that the response was due to the combined effects of increased parasympathetic cholinergic activity and withdrawal of a-adrenergic tone.…”
Section: Efferent Pathwaysmentioning
confidence: 99%
“…Lung inflation or activation of pulmonary receptors by foreign chemical agents has been shown to cause increases in coronary blood flow (Vatner & McRitchie, 1975;Clozel, Roberts, Hoffman, Coleridge & Coleridge, 1985;Ordway & Pitetti, 1986). In the studies which used chemical stimuli, myocardial blood flow was shown to increase in both subendocardial and subepicardial layers of the ventricle.…”
Section: Carotid Body Chemoreceptorsmentioning
confidence: 99%